Probability and conditional expectation fundamentals for the empirical sciences - Steyer, Rolf; Nagel, Werner (Wiley, 2017)
Probability and Conditional Expectations bridges the gap between books on probability theory and statistics by providing the probabilistic concepts estimated and tested in analysis of variance, regression analysis, factor analysis, structural equation modeling, hierarchical linear models and analysis of qualitative data. The authors emphasize the theory of conditional expectations that is also fundamental to conditional independence and conditional distributions.--Provided by publisher.